EFEKTIVITAS MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI BDP1 SMK NEGERI 1 PANYABUNGAN - ., Yusro; Elindra, Rahmatika; Ardiana, Nunik (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
Abstract This research aims to determine the effectiveness of contextual learning on students' ability to understand mathematical concepts in class XI BDP1 SMK Negeri 1 Panyabungan. This can be seen from the way students answer the questions given by the teacher, where students cannot answer the questions according to the indicators of their ability to understand mathematical concepts. To overcome this problem, research suggests efforts to use contextual learning models. The population of this study was all class XI BDP with a total of 52 students. The sampling technique used was Cluster Sampling. The research sample was class XI BDP1 with ????5 students. The research method used was an experimental method with a One-group Pretest-Posttest design. And data collection techniques using observation and tests. Based on the calculation results, data was obtained that the average student score before using the contextual learning model was 6.68, when combined with the assessment criteria it fell into the